The relationship of nutrition knowledge, nutrition status, and level of understanding with the behavior of reading nutrition labels - Alfi Nur Akhfa (UHAMKA PRESS, 2021)
The purpose of this study was to identify and to analyze the relationship between nutrition knowledge, nutrition status, and level of understanding with University Muhammadiyah Prof Dr Hamka (UHAMKA). This study used a cross-sectional method with total sample of 133 students. The results showed that there was a relationship between nutrition knowledge, nutrition status, and level of understanding with the behavior of reading nutrition labels. Further research is needed to examine other factors that can influence the behavior of reading nutrition labels.